The Tower Enigma - Zakaria Ali, (Wacana Seni Journal of Arts Discourse, 2003)
Next to my sarang/lair/hideout/office is this waler tower that over the years has grown to symbolize isolation, solitude, pride, high-mindedness, detachment, a man comfortable with himself, his limitations, his dreams. I see me, at different time of the day, of the hour even, in changing moods, from elation to apathy, and the numerous shades in between.